New near-infrared rhodamine dyes with large Stokes shifts for sensitive sensing of intracellular pH changes and fluctuations. Issue 55 (21st June 2018) - Zhang, Yibin; Xia, Shuai; Fang, Mingxi; Mazi, Wafa; Zeng, Yanbo; Johnston, Taylor; Pap, Adam; Luck, Rudy L.; Liu, Haiying
Abstract : New near-infrared rhodamine dyes with large Stokes shifts were developed and applied for sensitive detection of cellular pH changes and fluctuations by incorporating an additional amine group with fused rings. Abstract : New near-infrared rhodamine dyes with large Stokes shifts were developed and applied for sensitive detection of cellular pH changes and fluctuations by incorporating an additional amine group with fused rings into the rhodamine dyes to enhance the electron donating ability of amine groups and improve the spectroscopic properties of the dyes.